GAMBARAN PEMBERIAN MAKANAN PRELAKTEAL PADA BAYI UMUR 1-12 BULAN - Helmi " Juliana; Oswati " Hasanah; Erwin " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Prelacteal food is kind of food which is given to newborn until 3 or 4 days after birth, the food in form of solid and liquid except medicine and vitamin. The objective of this research is to know the overview of prelacteal feeding on baby age of 1 – 12 monthsat work area of Public health service Sebangar, Bengkalis regency, Riau Province. This research is simple descriptive with Clauster sampling. Population in this research is 669 babies which are located in 6 villages in work area of Sebangar public health service is taken as much 20 % from 6 villages that is 2 villages. Next on 2 villages, respondents were taken by accidental sample technic, where the researcher explains how is the overview of prelacteal feeding with data collected or information in objective way. The research was done to 87 mothers whohave baby age of1 – 12 months in two villages they are Batinsobanga village and KesumbuAmpai village. The analysis used was Univariat analysis which is done to analyze frequency distribution from each variable prelacteal feeding. The result of the research shows that most of respondents give prelacteal food (78,2%).Prelacteal food time given,almost the respondent give to baby age of 1day (52,9%). Based on the kinds of prelacteal food, most of respondents give in the form of liquid food (39,1%) and based on the reason prelacteal feeding, most of respondents said it was to contend with fussy baby (33,3%). The result of this research recommend to all health provider to give continue education for people that nutrition need on newborn age of 1- 4 days will still be fulfilled without prelacteal food although  mother’s breast milk hasn’t come out.Keywords: Infants (1-12 months), Prelacteal Feeding